2021
DOI: 10.3389/fpls.2021.740240
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic Acid Preharvest Treatment Improves Colour and Quality of Seedless Table Grape ‘Magenta’ Upregulating on-Vine Abscisic Acid Metabolism, Relative VvNCED1 Gene Expression, and the Antioxidant System in Berries

Abstract: Graphical Abstract 1Experimental design for oxalic acid preharvest treatment and main results from a metabolomic approach on increasing colour and quality of table grape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Conversely, DPA concentration was ten times lower than ABA in agreement with a previous study by Garcıá-Pastor et al (2021a) on 'Magenta' table grape. DPA showed an increasing trend, particularly during shelf life as seen in Pogańy et al (2020).…”
Section: Abscisic Acid Accumulation Can Regulate Grape Berry Metabolismsupporting
confidence: 92%
“…Conversely, DPA concentration was ten times lower than ABA in agreement with a previous study by Garcıá-Pastor et al (2021a) on 'Magenta' table grape. DPA showed an increasing trend, particularly during shelf life as seen in Pogańy et al (2020).…”
Section: Abscisic Acid Accumulation Can Regulate Grape Berry Metabolismsupporting
confidence: 92%
“…The positive effect of alginate coating with SA or OA, in minimizing loss of antioxidants, might be attributed to delayed oxidation of phenolics and enhanced the antioxidant enzymes. Enhanced of antioxidant in response to preharvest SA or OA application has also been reported in grapes (García-Pastor et al, 2021;Nia et al, 2022). Moreover, alginate coatings, restricted moisture loss and gas exchange, was reported effective in retaining higher antioxidants than control in sweet cherry and mango (Diaz-Mula et al, 2012;Rastegar et al, 2019).…”
Section: Antioxidantsmentioning
confidence: 75%
“…Since TPC was negatively correlated with weight loss and decay amount, TPC amount was found to be lower in control fruits due to increased weight loss and decay. It has been reported that the application of elicitors such as alginate, SA and OA improves the polyphenol content in fruits and thus increases their quality (Konuk Takma and Korel, 2017;Kok and Bal, 2019;Gomes et al, 2021;García-Pastor et al, 2021). These results indicate that SA and OA applications promoted TPC accumulation during storage due to activation of PAL, a key enzyme of the phenylpropanoid pathway (Shen and Yang, 2017;Martinez-Espla et al, 2019).…”
Section: Total Phenol Contentmentioning
confidence: 80%
See 1 more Smart Citation
“…In plants, 9-cis-epoxycarotenoid dioxygenase (NCED) function as a pivotal enzyme in abscisic acid (ABA) biosynthesis and can drive the specific cleavage of 9-cis-epoxycarotenoids to produce the essential ABA precursor, xanthoxin [4][5][6]. Long-term studies have shown that the endogenous hormone abscisic acid (ABA) is intricately linked to regulating drought resistance in some plants [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%